Emotional intelligence and its relationship to guidance creativity among educational counselors. (Journal of the College of Basic Education, 2025)
The current research aimed to identify emotional intelligence among educational counselors, and the significance of differences in emotional intelligence among educational counselors according to the gender variable (males/females ), and guidance creativity among educational counselors, and the significance of differences in guidance creativity among educational counselors according to the gender variable (males/females), and the relationship between emotional intelligence and guidance creativity among educational counselors. The research sample was chosen from educational counselors in schools affiliated with the General Directorate of Education in Anbar and amounted to (300) male and female counselors. To achieve the research objectives, a scale for emotional intelligence was constructed, and a scale (Ali, 2023) was adopted to measure guidance creativity. The researcher relied on the statistical package (SPSS) in analyzing the research data, and reached the following results: *- Educational counselors possess emotional intelligence.*- Differences in emotional intelligence are statistically significant according to the variable (gender) and in favor of females.*- Educational counselors possess guidance creativity.*- There are no statistically significant differences according to the variable (gender) in guidance creativity.*- There is a positive (direct) correlation between emotional intelligence and guidance creativity among educational counselors.The researcher reached a set of recommendations and proposals